Intuition and Reason: An Indian Approach - Nandhikkara, Jose; Chethimattam, J. B. (Journal of Dharma, 1976)
Aristophanes reports the visit of an Indian philosopher to Socrates. Socrates told the easterner that his work consisted in investigations about the life of men. The Indian philosopher smiled and remarked that no one could understand things human without understanding first things divine. Referring to this alleged dialogue S. Radhakrishnan says that it suggests that "for the whole Western tradition man is essentially a rational being, one who can think logically and act in a utilitarian manner", while the Indian thinkers hold that "we possess a power more interior than intellect by which we become aware of the real in its intimate individuality and not merely in its superficial or discernible aspects." This may sound an over-simplification. But it points to a radical difference in the logical approaches of East and West, regarding the pilgrimage of human reason from timespace bound daily experience to the timeless reality that can be grasped only through intuition.